2020
DOI: 10.1016/j.fuel.2020.117615
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-dependent alterations of static and dynamic contact angles in oil/brine/calcite systems: A molecular dynamics simulation study

Abstract: In this study, classic Molecular Dynamics (MD) simulations with established force fields were first performed to investigate the salinity effects on the static contact angle of a n-decane droplet immersing in the water atmosphere within a calcite nanochannel to advance our microscopic understanding on low salinity flooding. By applying an external body force, dynamic contact angle of n-decane in the water phase was also studied in the presence of various salt concentrations based on Non-Equilibrium MD (NEMD) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…21 In later work, the salinity-dependent deformation of a nanodroplet of n-decane on a calcite substrate was studied, and the reduction of contact angle correlated to the increasing salt concentration of the aqueous environment. 22 Recently, Koleini et al observed a direct relationship between the extent of benzoic acid adsorption onto calcite and the concentration of sodium cations in the aqueous interface region. 23 They also pointed out the importance of ion pairing in the brine film separating hydrocarbon phases and the pore wall of carbonates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21 In later work, the salinity-dependent deformation of a nanodroplet of n-decane on a calcite substrate was studied, and the reduction of contact angle correlated to the increasing salt concentration of the aqueous environment. 22 Recently, Koleini et al observed a direct relationship between the extent of benzoic acid adsorption onto calcite and the concentration of sodium cations in the aqueous interface region. 23 They also pointed out the importance of ion pairing in the brine film separating hydrocarbon phases and the pore wall of carbonates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this model, the parallel Simulator (LAMMPS) free software package (Mehana et al 2018;Zhao et al 2020;Liu et al 2017b;Yan et al 2017b) was used and the simulation results were visualized and processed by VMD and Ovito. The structure of each molecule is first optimized, followed by the optimization of the potential energy of the initial configuration.…”
Section: Methods and Modelsmentioning
confidence: 99%
“…Yu et al (2020) studied the contact angle of water and brine as a function of temperature, pressure, salinity, ion type, and gas content by using MD simulation and compared the results with the literature data. Zhao et al (2020) 2021) studied the intermolecular interactions between crude oil compositions including saturated hydrocarbons, aromatic hydrocarbons, resins, asphaltenes, and amphoteric surfactants 3-(decyl dimethylhydrazone) propane-1-sulfonates (DDPS). From the research mentioned above, it is exemplified that the molecular dynamics simulation technique has been an effective tool to study flow and displacement at the nanoscale (Fang 2019;Fang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However considering the multiple influential factors, a clear understanding of the AO impact effects leading to the disintegration is still experimentally challenging [21][22][23]. To this end, molecular dynamics (MD) simulations can be used as an alternative to investigate AO degradation mechanisms on solid surfaces [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%